A novel axial pattern skin flap based on the lateral thoracic artery in the dog - Anderson, D. M.; Charlesworthi, T. C.; White, R. A. S. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
The cutaneous distribution and anatomical landmarks of the lateral thoracic artery in the dog are reported. Perfusion studies in cadavers showed a variable distribution, but a skin flap capable of rotation through 90° could be created. The successful use of an axial pattern skin flap based on the lateral thoracic artery for reconstruction of a major skin deficit over the caudal elbow of a Greyhound is reported.
Keywords: Skin flap; lateral thoracic; reconstruction Vet Comp Orthop Traumatol 2004; 17: 73-7